An autopsy study of sudden cardiac death in persons aged 1–40 years in Brescia (Italy). Issue 6 (June 2016) - Vassalini, Marzia; Verzeletti, Andrea; Restori, Mario; De Ferrari, Francesco
Abstract : Introduction: Sudden cardiac death (SCD), above all when occurring in young people, remains a major clinical problem. We have analysed the clinical and post mortem findings of patients who were evaluated for SCD. Methods and results: We have analysed 54 cases of SCD which occurred in patients aged below 40 years during the period 1993–2012 and were studied at the Institute of Forensic Medicine of Brescia. The following variables were considered: sex, age, medical history, autopsy findings with special reference to macroscopic and histological evaluation of the heart and toxicological investigation. In all cases, we also performed the dissection of the cardiac conduction tissue with subsequent serial sampling and careful microscopic evaluation. Most SCD patients were men (76%), with a mean age of 27 years. The results of post mortem investigations have identified the following abnormalities: coronary artery disease (18.5%), arrhythmogenic right ventricular dysplasia (11.1%), hypertrophic obstructive cardiomyopathy (9.2%), severe valvular heart disease (7.4%) and myocarditis (7.4%). A case of persistence of the inter-atrial communication with cardiomegaly and right and left ventricular hypertrophy was also reported. Examination of the cardiac conduction tissue showed abnormalities in 12 cases (22.2%), in whom the heart was structurally normal at macroscopic examination. Despite all the investigations carried out, any pathogenic substrate that could have justified death was not found in 12 cases (22.2%). Conclusion: Our study underlines the value of an accurate routine post mortem investigation that may show an otherwise unsuspected structural heart disease. The serial study of the conduction tissue may provide pathologic substrates that may be responsible for the arrhythmic cause of death. A meaningful percentage of cases (22%) had no evidence of any abnormality. Genetic testing can be indicated in these cases.